METABOLIC DYSFUNCTIONS OF PERIPUBERTAL PROTEIN RESTRICTION IN MALE RATS - Gabriel Kian Guimarães Lopes; Anna R. O. Ferreira; Maiara V. G. Ribeiro; Maria N. C. Peres; Leticia F. Barbosa; Scarlett R. Raposo; Mariana D. Fernandes; Marcos V. Martins; Douglas L. Almeida; Paulo Cezar de Freitas Mathias (Arquivos do Mudi, 2023)
The current study investigate sound effects of low-protein diet (LP) during peripubertal periodto induce metabolic dysfunctions. In our study (CEUA 2910011021), 30 days-old Wistar malerats received LP (4% protein) and control rats were fed a 20.5% protein diet, for 60 days (NPgroup). Biometric parameters was taken and glucose, total and HDL-cholesterol, andtriglycerides were evaluated from plasma samples. Glycemia homeostasis was evaluated byOGTT and ITT, while hepatic parameters, including quantitative analysis of fat, triglyceridesand cholesterol in the liver was evaluated ex vivo. At 60 days, LP rats showed inferior bodymass (P=0.003), food intake (P=0.05), and nose-tail length (P=0.0001), compared to NP.Regarding biochemical assays, LP rats showed higher serum glucose (P=0.008); however,triglyceride (P=0.002), total cholesterol (P=0.02), and HDL levels (P<0.0001) were lower inLP animals compared to NP group. LP rats also had minor glucose tolerance (P=0.02) andgreater insulin sensitivity (P=0.01). In the hepatic parameters, LP rats showed an increase inliver fat (P<0.0001), hepatic triglycerides (P<0.0001), cholesterol (P<0.0001), and liverweight (P<0.0001). Considering the present data, peripuberty protein restriction inducedmetabolic and hepatic dysfunctions at the end of puberty. Therefore, malnourished adolescentanimals are at higher risk of developing metabolic syndrome in adulthood.